Design of Modular Power Management and Attitude Control Subsystems for a Microsatellite - Anwar Ali; Shoaib Ahmed Khan; M. Usman Khan; Haider Ali; M. Rizwan Mughal; Jaan Praks (International Journal of Aerospace Engineering)
The Electric Power System (EPS) and attitude control system (ACS) are the essential components of any satellite. EPS and ACS efficiency and compactness are substantial for the proper operation and performance of the satellite’s entire mission life. So, realizing the significance of EPS and ACS subsystems for any satellite, they have been assimilated and developed in modular forms focusing on efficiency and compactness. The EPS is comprised of three modules called the solar panel module (SPM), power conditioning module (PCM), and power distribution module (PDM) while the ACS has an embedded magnetorquer coil. For compactness and miniaturization purposes, the magnetorquer coil is embedded inside the SPM. The components used are commercial off-the-shelf (COTS) components emphasizing on their power efficiency, small dimensions, and weight. Latch-up protection systems have been designed and analyzed for CMOS-based COTS components, in order to make them suitable for space radioactive environment. The main design features are modularity, redundancy, power efficiency, and to avoid single component failure. The modular development of the EPS and ACS helps to reuse them for future missions, and as a result, the overall budget, development, and testing time and cost are reduced. A specific satellite mission can be achieved by reassembling the required subsystems.